Autonomy-connectedness, gender and culture: a comparative study on the interplay of personality functioning and social context - Moleiro, C.; Marto, L.; Santos, J. M.; Ratinho, I. (Portuguese Journal of Social Science, 2019)
Autonomy-connectedness refers to the need and ability the individual has for selfgovernance, as well as the capacity for intimacy and interpersonal relationships. The present study aimed to examine and compare participants (N=121) of four different cultural groups, namely Portuguese natives as well as Brazilian, British and Ukrainian immigrants residing in Portugal, on the different autonomy-connectedness components (self-awareness: SA; sensitivity to others: SO; capacity for managing new situations: CMNS). It also aimed at investigating the relationship between autonomy-connectedness and acculturation among the groups of immigrants. The results showed significant gender differences and among the cultural groups on SO. Adherence to the heritage culture was associated with the distinct dimensions of autonomy-connectedness differently for the various groups, and time of residence was also key in how the dimensions were endorsed cross time. This study contributes to the theoretical framework of the concept of autonomy-connectedness in light of cross-cultural perspectives.